2021
DOI: 10.21203/rs.3.rs-288103/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distributed context-dependent choice information in mouse dorsal-parietal cortex

Abstract: Choice information appears in the brain as distributed signals with top-down and bottom-up components that together support decision-making computations. In sensory and associative cortical regions, the presence of choice signals, their strength, and area specificity are known to be elusive and changeable, limiting a cohesive understanding of their computational significance. In this study, examining the mesoscale activity in mouse posterior cortex during a complex visual discrimination task, we found that bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Experimental observations made at the local-circuits level [84] and at the multi-area level [70], have shown that visual and motor signals, concurrently activating visual areas, can be represented by distinct low-dimensional activity manifolds, that, at the mesoscale level, are near orthogonal to each other [85]. Therefore, we next examined the propagation of visual and motor signals across layers and the separation of the representations.…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…Experimental observations made at the local-circuits level [84] and at the multi-area level [70], have shown that visual and motor signals, concurrently activating visual areas, can be represented by distinct low-dimensional activity manifolds, that, at the mesoscale level, are near orthogonal to each other [85]. Therefore, we next examined the propagation of visual and motor signals across layers and the separation of the representations.…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…As described in Orlandi et. al., 2021 [94], the awake mice were head-fixed and placed under a dual cube THT macroscope (Brainvision Inc.) for widefield imaging in tandem-lens epifluorescence configuration using two AF NIKKOR 50 mm f/1.4D lenses. We imaged the jGCaMP7f fluorescence signals using interleaved shutter-controlled blue and violet LEDs with a CMOS camera (PCO Edge 5.5) with an acquisition framerate of 60 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…Then, as described in Orlandi et. al., 2021 [94], we corrected for the “hemodynamic component” by removing a calcium-independent component from the recorded signal. For every pixel, the blue and violet data were independently transformed into a relative fluorescence signal, Δ F/F = ( F − aF − b ) /b , where F is the original data, and the a and b coefficients are obtained by linear fitting each time series, i.e., F ( t ) ≈ at − b .…”
Section: Methodsmentioning
confidence: 99%